Pengaruh Penambahan Jantung Pisang Terhadap Nilai pH dan Sensoris Bakso Daging Rusa (Cervus Timorensis) - Dyan Wahyu Pribadi; Dirwan Muchlis; Aloysia Tenny Damayanti Indriastuti (Universitas Musamus, Merauke, Papua, 2018)
This research aims to know the influence of the banana inflorescence addition of pH values andsensory venison meatballs. The method used is complete randomized design (CRD), method consisting of 5treatments and 3 replicates. Treatment 1 = A1 (100 grams banana heart and 100 grams of venison), 2 = A2treatment (80 grams of banana heart and 120 grams of venison), 3 = A3 treatment (60 gram banana heartand 140 grams venison), 4 = A4 (40 grams of banana heart and 160 grams of venison), treatment 5 = A5(20 grams of banana heart and 180 grams venison). The observed parameters are pH test meatballs andorganoleptic of color, the taste, flavor, and texture. pH test result obtained at pH values of highest meatballsA2 treatment namely 5.6, while organoleptic the test results show that the only scent that does not differmarkedly, while the color, the taste, the texture, the real power of different receipt (P>0.05)